Rahasia Kesuksesan Bisnis Property: Eksplorasi Pengaruh Firm Size, Struktur Modal dan Profitabilitas - Suha Wulandari; Ana Kadarningsih (Akuntansi, 2023)
This study aims to examine the influence of firm size, capital structure, and profitability on the value of companies in the Property and Real Estate sector listed on the Indonesia Stock Exchange from 2018 to 2022. The research population comprises 85 companies, with a sample of 48 companies selected using purposive sampling. The analysis was conducted using SPSS version 24 as the analytical tool. The results of the analysis indicate that capital structure and profitability have a significant positive impact on the company's value, while firm size has a significant negative impact.